'SING, O BARREN ONE WHO DID NOT BEAR': CHILDLESSNESS, BLESSING AND VOCATION IN THE OLD TESTAMENT. Issue 2 (April 2019) - Warner, Meg
Abstract : In the Old Testament, fertility is closely associated with divine blessing, and infertility with the absence of divine blessing. If I am an infertile woman, reading the Old Testament today, how am I to understand this pattern in my own life? Am I not blessed? This article considers issues of context, both of the Old Testament and of today, arguing that the Old Testament speaks about questions of fertility with multiple voices. Although the production of children is foregrounded, the Old Testament presents other vocations as paths to divine blessing. In particular, service of the earth is singled out in the article as a vocation that is foregrounded by the Old Testament, that is blessed and that has particular application to our own context.